The Effect of Brand Image, Packaging, and Price Perception on Consumer Purchasing Decisions of Generation Z for Silverqueen Chocolate Valentine Edition in Surabaya - Amalia Tasya Salsabila Suyanto; Ugy Soebiantoro, (International Journal of Economics (IJEC), 2023)
The purpose of this research was to determine the effect of brand perception, packaging, and price perception on Generation Z consumers of SilverQueen chocolate in Surabaya. This quantitative research technique utilized a community of customers who have purchased the unique SilverQueen Valentine's Edition chocolates in Surabaya, Indonesia. Non-probability sampling method and purposive sampling methodology were used to collect 112 research samples from the population. An online survey was used to collect data, and a Likert scale was used to assess responses. Partial Least Square (PLS) analysis was used. The findings indicated that each variable had a significant effect on Generation Z consumers of SilverQueen chocolate in Surabaya, who make purchasing decisions based on brand image, packaging, and price considerations.